Answer:
Explanation:
We know that:
a : b = 1 : 2 (or a = (1/b)*b)
b : c = 3 : 4 (or b = (3/4)*c)
So, we can substitute the value of b from the second equation into the first equation to get the ratio of a : c:
a = (1/b)*b = (1/((3/4)c))((3/4)c) = (4/3)(1/c)*c = (4/3)*1 = 4/3
So, the ratio of a : c is 4 : 3.
Alternatively, we can use the cross-multiplication method to find the ratio.
a : b = 1 : 2, and b : c = 3 : 4
so a4 = b3, and b4 = c3
so a4 = c3
so a:c = 3:4
In this way also we got the ratio of a:c as 3:4